Compound Heterozygosity for a Novel Frameshift Variant Causing Fatal Infantile Liver Failure and Genotype-Phenotype Correlation of POLG c.3286C>T Variant - Kanokwan Sriwattanapong; Kitiwan Rojnueangnit; Thanakorn Theerapanon; Chalurmpon Srichomthong; Thantrira Porntaveetus; Vorasuk Shotelersuk (MDPI AG, 2021)
A variant in the POLG gene is the leading cause of a heterogeneous group of mitochondrial disorders. No definitive treatment is currently available. Prenatal and newborn screening have the potential to improve clinical outcome of patients affected with POLG-related disorders. We reported a 4-month-old infant who presented with developmental delay, fever, and diarrhea. Within two weeks after hospital admission, the patient developed hepatic failure and died. Liver necropsy demonstrated an extensive loss of hepatocytes and bile duct proliferations. Trio-whole exome sequencing identified that the patient was compound heterozygous for a novel frameshift variant c.3102delG (p.Lys1035Serfs*59) and a common variant c.3286C>T (p.Arg1096Cys) in POLG (NM_002693.3) inherited from the mother and father, respectively. The c.3102delG (p.Lys1035Serfs*59) was a null variant and classified as pathogenic according to the American College of Medical Genetics and Genomics Standards and Guidelines. Prenatal genetic screenings using rapid whole exome sequencing successfully detected the heterozygous c.3286C>T variant in the following pregnancy and the normal alleles in the other one. Both children had been healthy. We reviewed all 34 cases identified with the POLG c.3286C>T variant and found that all 15 compound heterozygous cases had two missense variants except our patient who had the truncating variant and showed the earliest disease onset, rapid deterioration, and the youngest death. All homozygous cases had disease onset before age 2 and developed seizure. Here, we report a novel POLG variant expanding the genotypic spectrum, demonstrate the successful use of exome sequencing for prenatal and neonatal screenings of POLG-related disorders, and show the genotype-phenotype correlation of the common c.3286C>T variant.